The juvenile street trader and the state: the problem of the waifs and strays - O'Connell, John Robert (Statistical and Social Inquiry Society of Ireland, 1912)
Tonight, I venture to call your attention to another aspect of the relation of the citizens of today to the citizens of tomorrow, and to ask you to consider the future of those who, though not officially pauper children, are in danger of becoming pauper adults, and the prospects of those who are not criminals at present, but whose feet are on the first steps of that road which ends in so many cases in a life of crime. Although this problem of the Juvenile Street Traders has not before this been brought under the consideration of this Society, it has received a considerable amount of public attention in other places in the past ten years.
Read Friday, 28th April, 1911
Keywords: Child labour; Street vendors; 314.15